(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article highlights the importance of translation as a means of communication in a globalized society. The article discusses the main theoretical aspects of translation, including its cultural and linguistic challenges. It also examines current trends and technologies influencing the practice of translation, as well as its role in strengthening intercultural interaction and exchange. Particular attention is paid to the adaptation and translation of content in various fields, including literature, media and academic research